A Subtle Threat to Urban Populations in Developing Countries: Low Back Pain and its Related Risk Factors. Issue 7 (April 2016) - Noormohammadpour, Pardis; Mansournia, Mohammad Ali; Asadi-Lari, Mohsen; Nourian, Ruhollah; Rostami, Mohsen; Kordi, Ramin
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: A cross-sectional, population-based survey. Objective: The aim of this study was to estimate the prevalence, and biological and psychological correlates of low back pain (LBP) in large, populated urban areas. Summary of Background Data: LBP is a common and costly medical problem all around the world. Currently, there are limited data available on prevalence as well as biological and psychological correlates of LBP in large urban populations in developing countries. Methods: Here, in a cross-sectional, population-based survey, we analyzed data obtained from 22, 952 subjects living in Tehran. Results: Chronic, 1-year, and point prevalence of LBP among subjects were 12.2%, 42.1%, and 36.2%, respectively. LBP was more prevalent among older population, women, housewives, and obese people after adjustment for confounding factors using logistic regression models. In addition, persons with a general health questionnaire (GHQ-28) score ≥6 were about 2 times more likely to experience LBP in comparison with others. Both subjects with higher educational levels and those who were never married reported significantly less LBP. Furthermore, we could not find any significant correlation between smoking and physical activity level with LBP. Conclusion: LBP is prevalent among the general population of Tehran. Our findings can help health care providers regarding logical assignment of limited resources, in order to create multidimensional prevention plans according to potentially modifiable associated factors. Level of Evidence: 3